Estudo da cinética de biodegradação de efluente com alta concentração de ácidos graxos - Nascimento, Rogério do (2009)
This work is a study on the kinetics of anaerobic degradation of effluent with a high concentration of lipids, particularly fatty acids, acetic acid and oleic acid, having as a parameter for measuring the degradation chemical oxygen demand (COD). Based on these studies, we decided to conduct an experiment of degradation of the effluent in question in anaerobic batch, and periodically conducted sampling for analysis of total fatty acid concentration, free fatty acid, oleic acid and COD. The results showed the efficient biodegradation of these substrates in the reactor, and the consequent reduction of COD load in the effluent. The experimental data were used to survey the kinetics of the process, using them to establish, through mathematical modeling, the values of kinetic parameters and obtain the optimal values of these with the use of the method of particle swarm. Both the experimental data, the mathematical modeling showed the interaction between the substrates present in the process, for example, the preference for degrading microbial consortium in the free fatty acids and oleic acid relative to acetic acid. It has also been possible to demonstrate a latency period of the process, the consumption of organic matter through the profile of COD, due to the formation of free fatty acids and oleic acid. And, the subsequent reduction of these parameters so that these substrates have begun to be degraded. From a practical standpoint, this work suggests good efficiency in applying this technology, biodegradation in the treatment of effluents containing high levels of lipids.